The Effects of Exposure to Recent Autobiographical Events on Declarative Memory in Amnestic Mild Cognitive Impairment: A Preliminary Pilot Study - Gelonch, Olga; Cano, Neus; Vancells, Marta; Bolaños, Marc; Farràs-Permanyer, Laia; Garolera, Maite (Current Alzheimer Research, 2020)
Background: Individuals with amnestic Mild Cognitive Impairment (aMCI) are at heightened risk of developing Alzheimer's dementia. In recent years, much attention has been given to the search for new interventions to slow down the progression of cognitive decline of these patients. Wearable digital camera devices are one form of new technology that captures images of one’s life events, so they constitute a promising method to be used as a means to stimulate recent autobiographical memory. Objective: This preliminary study investigates the ability of a new cognitive intervention based on exposure to recent autobiographical memory captured by wearable cameras to improve episodic memory in patients with aMCI. Methods: Seventeen subjects wore a wearable camera while they went about their daily activities. The images captured were converted into eight different 3-minute films containing the most relevant information of each event. The intervention involved eight individualized weekly sessions during which patients were exposed to a different autobiographical event each week. Besides, several specific questions were formulated within each session. Clinical questionnaires assessing cognitive reserve, premorbid intelligence, depression, and anxiety were administered at baseline. Measures of objective episodic memory were applied at baseline and at post-treatment. Results: Significant improvements were observed at post-treatment in memory measures, and significant associations were found between memory change scores and age and cognitive reserve. Anyway, these associations did not reach statistical significance after adjusting for multiple comparisons. Conclusion: The present study provides preliminary evidence that aMCI patients may benefit from a cognitive intervention program based on re-experiencing recent autobiographical events. However, future studies incorporating a control group will be needed to confirm these preliminary findings.
Keywords: episodic memory